Variable ageing and storage of dissolved organic components in the open ocean - Loh, A. N.; Bauer, J. E.; Druffel, E. R. M. (Nature, 2004)
Seawater dissolved organic matter (DOM) is the largest reservoir of exchangeable organic carbon in the ocean, comparable in quantity to atmospheric carbon dioxide(1,2). The composition, turnover times and fate of all but a few planktonic constituents of this material are, however, largely unknown(3,4). Models of ocean carbon cycling are thus limited by the need for information on temporal scales of carbon storage in DOM subcomponents, produced via the 'biological pump', relative to their recycling by bacteria(3,4). Here we show that carbohydrate- and protein-like substances in the open Atlantic and Pacific oceans, though often significantly aged, comprise younger fractions of the DOM, whereas dissolved lipophilic material exhibits up to similar to90 per cent fossil character. In contrast to the millennial mean ages of DOM observed throughout the water column, weighted mean turnover times of DOM in the surface ocean are only decadal in magnitude. An observed size-age continuum further demonstrates that small dissolved molecules are the most highly aged forms of organic matter, cycling much more slowly than larger, younger dissolved and particulate precursors, and directly links oceanic organic matter age and size with reactivity(3,5).
847daTimes Cited:93Cited References Count:30